Literature Review Regarding PCK of Chemistry Teachers and Prospective Chemistry Teachers - Rabiatul Adawiyah; Alessandro Jeremi Manarisip; Suyanta Suyanta (Postgraduate, University of Mataram, 2023)
This research aims to provide an overview of the research methodology used in conducting a literature review of 21 journals indexed by Scopus and included in the Q1 category during the 2013-2022 period. This research uses a literature review method, this method is a scientific approach that provides a comprehensive picture of the development of a research topic. Through this literature review, researchers can obtain information regarding the year of publication, research methods applied, instruments used in each journal, and the focus of studies conducted by each journal. At the results and discussion stage, this research details the concept of Z score as a statistical value, factor analysis, correlation between factors, and coding analysis in the context of qualitative research. The concept of in-depth analysis which includes an in-depth examination of a subject or phenomenon is also discussed in detail. In addition, various research methods such as constant-comparative, person map items, PCS, TSPCK rubric, questionnaires, interviews, observation, and documentation are explained in depth. The importance of pedagogical competence in implementing the educational process is in the main spotlight, and analysis of the literature in the journal